Biostimulants Enhanced Seedling Root Growth and Bulb Yields of True Seed Shallots (Allium cepa var aggregatum L.) - I.G.A.M.S., gung; I.W., Diara (International Journal of Environment, Agriculture and Biotechnology, 2019)
The objective of this research was to investigate the effects of biostimulan (PGPR) on root growth of seedlings and bulb yields of true seeds shallots (TSS). The research was conducted in the glasshouse in Tangtu village, Badung regency,Bali province of Indonesia, from April until October 2018. Complete randomized block design was used with 4 replications. Three kinds of biostimulants (B, C, D) and one control, and two TSS varieties (Sunren F1 and Tuktuk) were the treatments imposed. Results of experiment showed that biostimulants as well as TSS variety significantly (P<0.05) increased germination percentage, root length of TSS seedlings, leaf chlorophyll content, bulb diameter, bulb number, leaf and bulb fresh weight per pot. However there was no significant different effect between types of biostimulant. Interaction effect between biostimulants and TSS variety was only significant on leaf chlorophyll content. Biostimulant application could be expected to increase growth and yields of TSS.